Clinical supervisory approaches that are perceived to promote or hinder motivation amongst audiology students: a qualitative investigation - Jamaluddin, Saiful Adli; Ali Hanafiah, Nurlin; Milatu Samsi, Nur Fizah Hayani (International Islamic University Malaysia, 2024)
Mentoring students in the clinics through clinical supervision is a crucial part of providing them with real-world experience, but not much is known about effective supervision techniques in the field of audiology. Background: The purpose of this study is to explore the characteristics of clinical supervision that motivate and demotivate students’ learning during their undergraduate study. Methods: A qualitative descriptive study approach was applied as it enabled in-depth exploration of students’ opinions on supervisory approaches based on their experiences during undergraduate study. Interviews had been carried out among ten graduating Audiology students from the International Islamic University Malaysia, Kuantan. Results: Seven themes emerged from the qualitative content analysis which were constructive behaviour during discussion, positive interaction between students and supervisors, constructive behaviour during testing, unconstructive behaviour during discussion, unconstructive behaviour during testing, conflicting approaches between supervisors, and negative attitude towards students. Conclusion: Actions that negatively affect students' motivation should be identified and addressed, while actions that positively affect students' motivation should be maintained and internalized to help students advance their audiology abilities.